2021
DOI: 10.3390/ijerph18137161
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Psychosocial Impacts of the Different Restrictive Measures during One Year into the COVID-19 Pandemic on Patients with Cancer in Italy: An Ecological Study

Abstract: Background: The aim of the study was to assess the perceived quality of life and the psychosocial impact of the various restrictive measures due to COVID-19 pandemic on cancer patients in Italy, as well as their perception of the relationship with doctors and caregivers. Methods: This study compares three population-based observational studies of patients with cancer carried out in three consecutive time periods characterized by different restrictive measures using a self-administered online questionnaire. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
(51 reference statements)
1
10
0
Order By: Relevance
“…From the outset, the COVID-19 pandemic had a significant negative impact on people’s mental health [ 3 , 4 , 5 ]. For example, Ferrara et al [ 6 ] reported that the COVID-19 disease and the restrictive government measures harmed the mental health of individuals around the world, causing fear, frustration, anger and a long list of complex negative emotions. This result was also confirmed by Sánchez et al [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…From the outset, the COVID-19 pandemic had a significant negative impact on people’s mental health [ 3 , 4 , 5 ]. For example, Ferrara et al [ 6 ] reported that the COVID-19 disease and the restrictive government measures harmed the mental health of individuals around the world, causing fear, frustration, anger and a long list of complex negative emotions. This result was also confirmed by Sánchez et al [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the Tysi ąc-Miśta study, it was the first month of the pandemic (April 2020). As indicated by Ferrara et al in their study [18], the impact of the pandemic on anxiety, depression, and stress was highest in the first weeks of the pandemic and changed with time. This is at variance with the limited professional activity that took place in the first months of the pandemic in Poland, when the vast majority of offices were closed.…”
Section: Discussionmentioning
confidence: 64%
“…In the case of the Tysiąc-Miśta study, it was the first month of the pandemic (April 2020). As indicated by Ferrara et al in their study [ 18 ], the impact of the pandemic on anxiety, depression, and stress was highest in the first weeks of the pandemic and changed with time.…”
Section: Discussionmentioning
confidence: 93%
“…Further research reported that restrictive measures forced individuals to modify their lifestyles; their risk perceptions; their confidence in others and in institutions; their sense of community; and their perceived self-efficacy [ 8 , 9 ]. Female gender, younger age, occupational status (employed), lower perceived wellbeing, and health risk factors and diseases, such as cancer, were predictors of mental health symptoms that were correlated with the COVID-19 pandemic and restrictive measures for public safety [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%